Consumption of Lutein and Zeaxanthin and Its Relation to the Level of Macular Pigment Optical Density in Thai Subjects - Wipada Sae-Lao; Kansuda Wunjuntuk; Taweesak Techakriengkrai; Prapaisri P Sirichakwal (Journal of Nutrition and Metabolism)
The aim of the study is to determine dietary lutein and zeaxanthin (L/Z) consumption and to evaluate its association with macular pigment optical density (MPOD) in Thai subjects. Methods. This study was a cross-sectional study. A total of 120 ophthalmologically healthy subjects aged between 40 and 72 years were recruited from Bangkok and the vicinity area. Demographic data were collected using a questionnaire, while a semiquantitative food frequency questionnaire assessed the L/Z intake. MPOD was determined using the reflectometry method (VISUCAM 500®, Carl Zeiss Meditec AG). Pearson’s correlation coefficient analyzed the relationship between L/Z consumption and MPOD. Results. The mean age of the participants was 50.7 ± 7.5 years. The mean consumption of L/Z was 3.03 ± 2.65 mg per day. The mean MPOD was 0.102 ± 0.023 density units. Consumption of foods rich in L/Z, including ivy gourd (r = 0.217, p<0.05), Chinese flowering cabbage (r = 0.194, p<0.05), balsam pear (r = 0.193, p<0.05), lettuce (r = 0.182, p<0.05), sweet corn (r = 0.181, p<0.05), and pumpkin (r = 0.181, p<0.05), was positively associated with the mean optical density (mean MPOD). Consumption of green onion (r = 0.212, p<0.05) was positively associated with the sum of optical densities (MPOD volume). In contrast, chilli pepper consumption showed a negative association with mean MPOD (r = −0.220, p<0.05) and amaranth showed a negative association with MPOD volume (r = −0.283, p<0.05). No association was found between total L/Z consumption and MPOD. Conclusion. L/Z consumption is low among Thais living in Bangkok and the vicinity area, which may not be sufficient to ensure eye health, and total L/Z consumption is not associated with MPOD.